Durability aspects and bond strength of rubbercrete containing nano silica - Mohammed, B.S. (Canadian Society for Civil Engineering, 2015)
Accumulations of discarded scrap tires are non-biodegradable and have been a major concern. Even after long-period of landfill treatment, unmanaged waste tire poses environmental and health risk through fire hazard and as a breeding ground for disease carrying mosquitoes. Therefore, utilization of crumb rubber from this scrap tires for the production building materials in the construction industry would help to preserve the natural resources and also maintain the ecological balance. Inclusion of crumb rubber in concrete mixtures as partial replacement to fine aggregate will lead to improve the concrete (rubbercrete) properties such as thermal insulation performance, sound absorption and noise reduction coefficient and as well as the new rubbercrete will exhibits high capacity for absorbing plastic energy. However, in contrast with the normal concrete, the rubbercrete has lower strengths and durability. This adverse effect is attributed to the nature of the crumb rubber that repealing water and entrapping air on its surface which leads to lower bonding between cement matrix and crumb rubber particles. On the other hand, nano silica, nowadays, is widely used in the concrete as a filler to improve its strengths and durability. Therefore, in the research work reported in this paper, 15 rubberecrete mixtures containing different ratios of nano silica were cast and tested for compressive strength, bond strength and porosity. Results show increasing in the compressive and bond strengths and decreasing in porosity of rubbercrete mixtures containing nano silica in contrast with rubbercrete mixtures without nano silica. Â© (2015) by the Canadian Society for Civil Engineering All rights reserved.